Quantitative prediction of the drilling azimuth of horizontal wells in fractured tight sandstone based on reservoir geomechanics in the Ordos Basin, central China. (February 2022) - Liu, Jingshou; Zhang, Guanjie; Bai, Jianping; Ding, Wenlong; Yang, Haimeng; Liu, Yang
Abstract: Hydraulic fracturing and horizontal well technology can effectively improve reservoir production but can affect reservoir reconstruction through many factors, including the reservoir lithology, reservoir stress state and natural fractures. Considering tight sandstone as an example, the finite element method (FEM) and the optimal trajectory design scheme for a horizontal well are used in this study to determine the influence of the stress state, mechanical parameters and natural fractures of rock on the effects of hydraulic fracturing. Core reorientation via a paleomagnetic method is used to determine the natural fracture orientations in different well blocks. The in-situ stress magnitudes and directions are determined using microseismic monitoring of hydraulic fracturing, borehole breakout analysis, difference strain analysis and acoustic emission experiments. A heterogeneous geomechanical model is formulated based on log interpretations of the rock mechanical parameters of 111 wells and the results of triaxial mechanical experiments. The FEM is used to determine the in-situ stress field in the Dongrengou block. A predictive model for the hydraulic fracture propagation direction is formulated considering the in-situ stress, geomechanical model and natural fracture orientation. The results show that the mechanical parameters of the Dongrengou block are characterized by planar anisotropy and three-dimensional heterogeneity, where the rock mechanical parameters vary considerably across the plane and are vertically stratified. Using these results in conjunction with the drilling directions and oil production of 14 horizontal wells shows that oil and gas recovery is maximized by orienting horizontal wells perpendicular to the propagation direction of hydraulic fractures. Highlights: A method for quantitatively optimizing the drilling azimuth of horizontal wells in tight sandstone reservoirs. The planar anisotropy of the mechanical parameters leads to the absence of a conjugate fracture set. The direction of hydraulic fractures is affected by the tensile strength, stress difference and natural fractures. The in-situ stress and natural fractures are vertically stratified in the western Ordos Basin.